Partial left ventriculectomy improves left ventricular end systolic elastance in patients with idiopathic dilated cardiomyopathy - Gradinac, S (2000)
OBJECTIVE—To assess the effect of partial left ventriculectomy (PLV) on estimate of left ventricular end systolic elastance (Ees), arterial elastance, and ventriculoarterial coupling. PATIENTS—11 patients with idiopathic dilated cardiomyopathy before and two weeks after PLV, and 11( )controls. INTERVENTIONS—Single plane left ventricular angiography with simultaneous measurements of femoral artery pressure was performed during right heart pacing before and after load reduction. RESULTS—PLV increased mean (SD) Ees from 0.52 (0.27) to 1.47 (0.62) mm Hg/ml (p = 0.0004). The increase in Ees remained significant after correction for the change in left ventricular mass (p = 0.004) and end diastolic volume (p = 0.048). As PLV had no effect on arterial elastance, ventriculoarterial coupling improved from 3.25 (2.17) to 1.01 (0.93) (p = 0.017), thereby maximising left ventricular stroke work. CONCLUSION—It appears that PLV improves both Ees and ventriculoarterial coupling, thus increasing left ventricular work efficiency.   Keywords: dilated cardiomyopathy; elastance; partial left ventriculectomy